A gradient algorithm for optimal control problems with model-reality differences - Kek, S.L.; Aziz, M.I.A.; Teo, Kok Lay (American Institute of Mathematical Science, 2015)
In this paper, we propose a computational approach to solve a model-based optimal control problem. Our aim is to obtain the optimal solution of the nonlinear optimal control problem. Since the structures of both problems are dierent, only solving the model-based optimal control problem will not give the optimal solution of the nonlinear optimal control problem. In our approach, the adjusted parameters are added into the model used so as the dierences between the real plant and the model can be measured. On this basis, an expanded optimal control problem is introduced, where system optimization and parameter estimation are integrated interactively. The Hamiltonian function, which adjoins the cost function, the state equation and the additional constraints, is dened. By applying the calculus of variation, a set of the necessary optimality conditions, which denes modied model-based optimal control problem, parameter estimation problem and computation of modiers, is then derived. To obtain the optimal solution, the modied model-based optimal control problem is converted in a nonlinear programming problem through the canonical formulation, where the gradient formulation can be made. During the iterative procedure, the control sequences are generated as the admissible control law of the model used, together with the corresponding state sequences. Consequently, the optimal solution is updated repeatedly by the adjusted parameters. At the end of iteration, the converged solution approaches to the correct optimal solution of the original optimal control problem in spite of model-reality dierences. For illustration, two examples are studied and the results show the eciency of the approach proposed.